The German Experience: Evaluation of German Library Buildings from the Last Decades - Mittler, Elmar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The period after the Second World War was a golden age for library buildings in Germany — especially when investment in higher education was increased in the ‘Bildungsexpansion’. Typical examples of new and reconstructed buildings are checked against modern demands, based on a survey of the German university buildings in 2008. The paper gives an overview of the development of library architecture in Germany. It is a first case study for future evaluation activities in this field as well.